IMPLEMENTASI METODE PIXEL VALUE DIFFERENCING UNTUK PENYEMBUNYIAN PESAN PADA CITRA DIGITAL - Andri, Ricky; Hondro, Rivalri Kristianto; Tampubolon, Kennedi (STMIK Budi Darma, 2019)
The development of information technology is very fast, causing a lot of security holes that can be misused by people who are not responsible so that it can harm certain parties. Digital images are chosen as a container for inserting messages because digital images have sufficient size to hold the message and digital images are often used in information exchange so as not to invite suspicion from irresponsible parties. The information to be sent is hidden in a digital image, then the digital image is sent as normal data, so that third parties do not suspect that there is confidential information inside. Information that is hidden in the digital image can be extracted again by the recipient of the message. Pixel Value Differencing (PVD) works on a pair of adjacent pixel values (adjacent pixels). The advantage of the Pixel Value Differencing (PVD) method is that the capacity of the image generated to insert a message can be smaller than its original size, the processing time of this method is quite fast, after the message is inserted, the image quality has good quality. But this method also has disadvantages, because it is not resistant to manipulation.Keywords: Steganography, Digital Image, Pixel Value Differencing